An examination and evaluation of YTU library and documentation building in terms of building biology - Balanli, A; Ozturk, A; Karabiber, Z; Unver, R; Gedik, G; Yavuz, G; Vural, M (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
The physical and social characteristics of internal and external environments of the YTU Library Building were examined and the results were compared with the required levels and standards. Negative characteristics which may cause health problems on temporary and permanent users were determined, and potential health risks due to those characteristics were identified. (C) 2005 Published by Elsevier Ltd.
Keywords: building biology; university library building; physical environment; social environment; indoor environment; outdoor environment; health problems; Construction & Building Technology; Engineering